Methodology of average speed enforcement systems spot selection on Lithuanian roads and its evaluation - Gavėnienė, Laura; Matusevičius, Ernestas; Čygas, Donatas; Jateikienė, Laura; Vorobjovas, Viktoras; Čiuprinskas, Kęstutis (International Conference “Environmental Engineering”, 2023)
Average speed enforcement systems were installed on Lithuanian roads in 1 September, 2018. The Lithuanian Road Administration document, created on 29 April, 2020 No. V-60 “Methodology for creating a priority order for the selection and installation of average speed enforcement systems locations in Rural areas” determined where these systems should be installed. 81 road sections were selected by this method where was average speed enforcement systems have been installed. 12 road sections which length is higher than in document No. V-60 “Methodology for creating a priority order for the selection and installation of average speed enforcement systems locations in Rural areas” have been selected by the paper authors. The following parameters of road sections are analyzed in this paper: crossroads or exits lanes, traffic volume, number of road accidents, number of fatal and injury road accidents. Conclusions and recommendations for the methodology of road section selection are drawn at the end of this article.
Keywords: average speed enforcement systems; speed; road safety